2017
DOI: 10.1242/dmm.029561
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a multipurpose Prdm16 mouse allele by targeted gene trapping

Abstract: Gene trap mutagenesis is a powerful tool to create loss-of-function mutations in mice and other model organisms. Modifications of traditional gene trap cassettes, including addition of conditional features in the form of Flip-excision (FlEx) arrays to enable directional gene trap cassette inversions by Cre and Flpe site-specific recombinases, greatly enhanced their experimental potential. By taking advantage of these conditional gene trap cassettes, we developed a generic strategy for generating conditional mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…In Prdm16 KO brains, the prospective ChP in the lateral and the 3 rd ventricles are dramatically reduced (Fig. S1D, S1H-I, (Bjork et al, 2010b, Strassman et al, 2017), pointing to an essential role of PRDM16 in the ChP development. Together, the phenotypic analyses in…”
Section: Prdm16 Is Required For Neocortical Development and Choroid Pmentioning
confidence: 95%
“…In Prdm16 KO brains, the prospective ChP in the lateral and the 3 rd ventricles are dramatically reduced (Fig. S1D, S1H-I, (Bjork et al, 2010b, Strassman et al, 2017), pointing to an essential role of PRDM16 in the ChP development. Together, the phenotypic analyses in…”
Section: Prdm16 Is Required For Neocortical Development and Choroid Pmentioning
confidence: 95%
“…It is unknown whether the etiology of PR anomalies varies according to diagnostic category. There are excellent reviews of mandible, tongue, and palate development (e.g., [ 35 , 36 , 37 ]) and limited studies of mouse models that show PR phenotypes [ 38 , 39 , 40 , 41 ], but most studies are descriptive, without a focus on how these anomalies might be mechanistically, molecularly, or developmentally related.…”
Section: Uncertainty Of Diagnosismentioning
confidence: 99%
“…Nonsyndromic CP caused by an intronic Prdm16 splicing mutation in the cleft secondary palate 1 ( csp1 ) N -ethyl- N -nitrosurea-induced mouse model was thought to be the result of micrognathia and failed palate shelf elevation due to physical obstruction by the tongue, resembling human PR-like cleft secondary palate [ 38 ]. Conditional gene trap cassettes were used to develop a generic strategy for generating conditional mutations, validated in mice carrying a multipurpose allele of the Prdm16 transcription factor [ 39 ]. The phenotype of the Prdm16 cGT and Prdm16 cGTreinv mice was virtually identical to the previously reported Prdm16 csp1 phenotype [ 38 , 39 ].…”
Section: Development Of Pr Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the latter gene, prdm16 knockdown reduces expression of dlx2a and barx1 (Ding et al, 2013) as well as methylation of H3K4 and H3K9 (Shull et al, 2020). Loss of function by N‐ethyl‐N‐nitrosourea mutagenesis (Bjork, Turbe‐Doan, et al, 2010), RNA interference (Bjork, Fujiwara, et al, 2010), and gene trap (Strassman et al, 2017) revealed that it is required for palatogenesis in mice. Prdm16 is capable of binding the promoters of genes involved in myogenesis, chondrogenesis, and osteogenesis in cells of the developing mouse palate (Warner et al, 2012); expectedly, null mice exhibited increased expression of genes related to Tgfβ and Bmp signaling, as well as differential expression of genes involves in chondrogenesis and osteogenesis (Warner et al, 2013).…”
Section: Epigenetic Mechanisms Of Orofacial Cleftsmentioning
confidence: 99%